HeartWatch: Implementing a Pediatric Heart Center Program to Prevent Cardiac Arrests Outside the ICU. Issue 6 (7th November 2022) - Birely, Alexandra; Avula, Sravani; Butts, Ryan J.; Wolovits, Joshua S.; Lemler, Matthew S.; Hoffman, Olivia L.
Abstract : Introduction: Pediatric patients with cardiovascular disease are at increased risk of cardiopulmonary arrest. Despite utilization of Cardiac Pediatric Early Warning Scores to identify patients at risk of decompensation, our institution had a twofold increase in cardiac arrests (CAs) in the acute care cardiology unit (ACCU) over 2 years. Through a quality improvement initiative, we developed a watcher program, HeartWatch, to reduce the CA arrest rate in the ACCU by 50% over the first year of implementation. Methods: HeartWatch aims to identify patients not adequately captured by Cardiac Pediatric Early Warning Scores who are at high risk for sudden decompensation. Inclusion criteria were developed and evaluated during pilot and implemented phases (April 2020–April 2021) and then monitored in a sustained phase through June 2022. Our primary outcome was the reduction in the out-of-ICU CA rate. Results: During the 13 months, we enrolled 169 patients, and the CA rate decreased from 0.7 to 0.33 per 1, 000 patient days, a 53% reduction. The CA rate further decreased to 0.28 events per 1, 000 patient days, a 60% reduction, by June 2022. The most common indications for HeartWatch inclusion were high-risk single-ventricle patients (31%) and patients with diminished ventricular function (20%). Conclusions: Implementation of HeartWatch was associated with a meaningful reduction in CA in the ACCU. Creating shared mental models for high-risk patients is essential for patient safety. Future work will optimize local processes that focus on the sustainability of our gains. We will also evaluate opportunities to adapt and implement a similar framework in other institutions to assess reproducibility.